Symbiodinium sp. cells produce light‐induced intra‐ and extracellular singlet oxygen, which mediates photodamage of the photosynthetic apparatus and has the potential to interact with the animal host in coral symbiosis. Issue 2 (20th June 2016) - Rehman, Ateeq Ur; Szabó, Milán; Deák, Zsuzsanna; Sass, László; Larkum, Anthony; Ralph, Peter; Vass, Imre
Summary: Coral bleaching is an important environmental phenomenon, whose mechanism has not yet been clarified. The involvement of reactive oxygen species (ROS) has been implicated, but direct evidence of what species are involved, their location and their mechanisms of production remains unknown. Histidine‐mediated chemical trapping and singlet oxygen sensor green (SOSG) were used to detect intra‐ and extracellular singlet oxygen ( 1 O2 ) in Symbiodinium cultures. Inhibition of the Calvin–Benson cycle by thermal stress or high light promotes intracellular 1 O2 formation. Histidine addition, which decreases the amount of intracellular 1 O2, provides partial protection against photosystem II photoinactivation and chlorophyll (Chl) bleaching. 1 O2 production also occurs in cell‐free medium of Symbiodinium cultures, an effect that is enhanced under heat and light stress and can be attributed to the excretion of 1 O2 ‐sensitizing metabolites from the cells. Confocal microscopy imaging using SOSG showed most extracellular 1 O2 around the cell surface, but it is also produced across the medium distant from the cells. We demonstrate, for the first time, both intra‐ and extracellular 1 O2 production in Symbiodinium cultures. Intracellular 1 O2 is associated with photosystem II photodamage and pigment bleaching, whereas extracellular 1 O2 has the potential to mediate the breakdown of symbiotic interaction between zooxanthellae and their animal host during coral bleaching.